2004
DOI: 10.1093/jnci/djh006
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of BRCA1 and BRCA2 Mutations in Unselected Ashkenazi Jewish Patients With Colorectal Cancer

Abstract: Mutations in BRCA1 and BRCA2 that predispose to breast and ovarian cancer are detected in approximately 2.5% of the Ashkenazi Jewish population. To explore whether carriers of Ashkenazi founder mutations in BRCA1 or BRCA2 have an increased risk for colorectal cancer, we screened 586 unselected Ashkenazi Jewish case patients with colorectal cancer for the three common founder mutations in BRCA1 and BRCA2. We identified six carriers (1.02%) among these case patients. After adjusting for age at diagnosis and sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 21 publications
2
51
0
3
Order By: Relevance
“…DNA from case samples was analyzed for the three common Ashkenazi founder mutations in BRCA1 and BRCA2 (185delAG and 5182insC in BRCA1 and 6174delT in BRCA2) as described previously (14). Briefly, DNA was purified using the QiaAmp Blood DNA midi kit (Qiagen, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…DNA from case samples was analyzed for the three common Ashkenazi founder mutations in BRCA1 and BRCA2 (185delAG and 5182insC in BRCA1 and 6174delT in BRCA2) as described previously (14). Briefly, DNA was purified using the QiaAmp Blood DNA midi kit (Qiagen, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…4 Blood specimens were obtained regardless of ethnic origin and religion from 2002 to present. Before permanent anonymization of these samples, primary CRC diagnosis was confirmed by inspection of the electronic pathology record, and gender, religion, ethnic origin, history of chemotherapy, date of birth, age at diagnosis and date of diagnosis were recorded.…”
Section: Dear Sirmentioning
confidence: 99%
“…12 -15). Furthermore, it has been shown that mice deficient for either BRCA1 or BRCA2 develop a wide range of carcinomas, most commonly breast and lung but also endometrial, gastric, and colon cancer (12).Several studies in the past reported an increased risk of colorectal cancer in patients with BRCA1 or BRCA2 germ-line mutations (16 -19) whereas two more recent investigations could not confirm such an elevated risk (20,21). Loss of heterozygosity at the BRCA1 gene locus was shown to be Imaging, Diagnosis, Prognosis…”
mentioning
confidence: 99%
“…Several studies in the past reported an increased risk of colorectal cancer in patients with BRCA1 or BRCA2 germ-line mutations (16 -19) whereas two more recent investigations could not confirm such an elevated risk (20,21). Loss of heterozygosity at the BRCA1 gene locus was shown to be Imaging, Diagnosis, Prognosis…”
mentioning
confidence: 99%